Dysregulation of the Lysophosphatidylcholine/Autotaxin/Lysophosphatidic Acid Axis in Acute‐on‐Chronic Liver Failure Is Associated With Mortality and Systemic Inflammation by Lysophosphatidic Acid–Dependent Monocyte Activation. Issue 2 (15th June 2021) - Trovato, Francesca M.; Zia, Rabiya; Napoli, Salvatore; Wolfer, Kate; Huang, Xiaohong; Morgan, Phillip E.; Husbyn, Hannah; Elgosbi, Marwa; Lucangeli, Manuele; Miquel, Rosa; Wilson, Ian; Heaton, Nigel David; et al.
Abstract : Background & Aims: Acute‐on‐chronic liver failure (ACLF) is characterized by systemic inflammation, monocyte dysfunction, and susceptibility to infection. Lysophosphatidylcholines (LPCs) are immune‐active lipids whose metabolic regulation and effect on monocyte function in ACLF is open for study. Approaches & Results: Three hundred forty‐two subjects were recruited and characterized for blood lipid, cytokines, phospholipase (PLA), and autotaxin (ATX) concentration. Peripheral blood mononuclear cells and CD14 + monocytes were cultured with LPC, or its autotaxin (ATX)‐derived product, lysophosphatidic acid (LPA), with or without lipopolysaccharide stimulation and assessed for surface marker phenotype, cytokines production, ATX and LPA‐receptor expression, and phagocytosis. Hepatic ATX expression was determined by immunohistochemistry. Healthy volunteers and patients with sepsis or acute liver failure served as controls. ACLF serum was depleted in LPCs with up‐regulated LPA levels. Patients who died had lower LPC levels than survivors (area under the receiver operating characteristic curve, 0.94; P  < 0.001). Patients with high‐grade ACLF had the lowest LPC concentrations and these rose over the first 3 days of admission. ATX concentrations were higher in patients with AD and ACLF and correlated with Model for End‐Stage Liver Disease, Consortium on Chronic Liver Failure–Sequential Organ Failure Assessment, and LPC/LPA concentrations. Reduction in LPC correlated with higher monocyte Mer‐tyrosine‐kinase (MerTK) and CD163 expression. Plasma ATX concentrations rose dynamically during ACLF evolution, correlating with IL‐6 and TNF‐α, and were associated with increased hepatocyte ATX expression. ACLF patients had lower human leukocyte antigen‐DR isotype and higher CD163/MerTK monocyte expression than controls; both CD163/MerTK expression levels were reduced in ACLF ex vivo following LPA, but not LPC, treatment. LPA induced up‐regulation of proinflammatory cytokines by CD14 + cells without increasing phagocytic capacity. Conclusions: ATX up‐regulation in ACLF promotes LPA production from LPC. LPA suppresses MerTK/CD163 expression and increases monocyte proinflammatory cytokine production. This metabolic pathway could be investigated to therapeutically reprogram monocytes in ACLF.